2007
DOI: 10.1159/000107431
|View full text |Cite
|
Sign up to set email alerts
|

Facioscapulohumeral Muscular Dystrophy: A Multicenter Study on Hearing Function

Abstract: Facioscapulohumeral muscular dystrophy (FSHD) is an autosomal dominant progressive myopathy, characteristically associated with a 4q35 deletion. In the unusual infantile-onset form of this degenerative disease, sensorineural hearing loss is a frequent clinical manifestation, whereas in patients with typical late-onset FSHD, investigations regarding hearing impairment yielded controversial results. We describe the findings of a multicenter investigation on possible auditory impairment in a series of 73 FSHD pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 39 publications
2
23
0
1
Order By: Relevance
“…Interestingly, most of them experienced pain and fatigue, symptoms frequently reported by FSHD1 patients,31 and one of them (P3) had sensorineural hearing loss, a feature described in 25%–65% of FSHD1 patients 32. CK values were normal to twofold elevated, and muscle biopsy showed only mild dystrophic changes.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, most of them experienced pain and fatigue, symptoms frequently reported by FSHD1 patients,31 and one of them (P3) had sensorineural hearing loss, a feature described in 25%–65% of FSHD1 patients 32. CK values were normal to twofold elevated, and muscle biopsy showed only mild dystrophic changes.…”
Section: Resultsmentioning
confidence: 99%
“…Although retinal vascular abnormalities can be seen in up to 50% of patients with FSHD, symptomatic retinal disease (Coats syndrome) is quite rare . High frequency hearing loss has been reported in over half of FSHD patients, but the relevance of this has been questioned . One study suggested the level of hearing impairment is no greater than what would be expected for age .…”
Section: Discussionmentioning
confidence: 99%
“…High frequency hearing loss has been reported in over half of FSHD patients, but the relevance of this has been questioned . One study suggested the level of hearing impairment is no greater than what would be expected for age . That said, there is a subgroup of patients, typically with the largest contractions and earliest onset of disease, who require hearing aids …”
Section: Discussionmentioning
confidence: 99%
“…Specifically, muscle involvement was evaluated for each FSHD subject by a seven-grade 'Weakness Scale' (11,12), ranging from 0 (no weakness) to 7 (profound weakness in lower region muscles and/or severe or profound in upper region muscles) through grades I (mild weakness in scapulohumeral or in lower limb muscles), II (mild in both upper and lower region muscles), III (moderate in upper or lower region muscles), IV (moderate in both upper and lower region muscles), V (severe in upper or lower region muscles) and VI (severe in both upper and lower region muscles). Specifically, muscle involvement was evaluated for each FSHD subject by a seven-grade 'Weakness Scale' (11,12), ranging from 0 (no weakness) to 7 (profound weakness in lower region muscles and/or severe or profound in upper region muscles) through grades I (mild weakness in scapulohumeral or in lower limb muscles), II (mild in both upper and lower region muscles), III (moderate in upper or lower region muscles), IV (moderate in both upper and lower region muscles), V (severe in upper or lower region muscles) and VI (severe in both upper and lower region muscles).…”
Section: Patients and Diagnostic Criteriamentioning
confidence: 99%